An investigation of electron beam welding of Nb-1Zr-0.1C alloy: Process parameters and microstructural analysis. (August 2017) - Badgujar, B.P.; Kumar, Santosh; Jha, M.N; Samajdar, I.; Mascarenhas, M; Tewari, R.; Dey, G.K.
Abstract: Niobium based Nb-1Zr-0.1C alloy has been developed for high temperature applications. Welding of this alloy is difficult task due to its reactive nature, higher thermal conductivity and melting point. In the present work, Electron Beam (EB) welding technique, which can produce narrow deep penetration welds with nominal heat affected zone (HAZ) and minimum contamination, is used to weld the alloy. This work is aimed to produce the acceptable EB welds of Nb-1Zr-0.1C alloy. For this purpose, EB welds of Nb-alloy in bead-on-plate and square butt joint configurations were produced according to central composite design of the experiments with power (P) and weld speed (S) as input process parameters. The output of the welding process was measured in terms of depth of weld penetration (D), weld bead width (W), aspect ratio, joining efficiency and thermal efficiency. The correlations for D and W, as a function of process parameters, were obtained by non-linear statistical regression analysis. The weld joints produced were characterized by optical, Scanning Electron Microscopy (SEM) and Electron Back Scattering Diffraction (EBSD) techniques. The HAZ and base metal showed fine carbide precipitates along the grain boundaries, whereas carbides were found dissolved in the weld zone. The micro-hardness profile across the width of welds showed marginal increase in the hardness of weld zone and HAZ. Thermal and residual stress fields were estimated for the EB weld joint in square-butt configuration, using finite element technique and a good qualitative matching between the computed and experimental values was obtained. The detailed results of all these studies are described in this paper.